The Development of Solar Motor Generator for Stall Hawkers - Revindran, Marshal Franklyn; Fuad, Norfaiza (Evolution in Electrical and Electronic Engineering, 2023)
The increase in demand for energy stimulated by developing countries and the consequent decrease in power sources leads to an unsustainable future. This way renewable and clean energies are necessary to be practiced in our daily life. For instance, energy that produces through a movement or directly converted into electricity is known as kinetic energy. The present studies deal with the development of a Solar Motor Generator for stall hawkers, an innovation of a generator that generates electricity which will help us to produce electricity in a green way. This generator is a mini green energy power plant that converts chemical energy into usable electrical energy. The purpose of this generator is to produce both Alternating Current (AC) and Direct Current (DC) as the outputs. This generator will function as a normal motor generator where it will generate the current without any combustion process. This generator also consists of a solar panel in singular axis mode to track the position of the Sun. The evaluation of the parameter for the solar panel was verified and recorded. The following parameters were voltage (V) and current (I). The parameters’ readings are obtained every 7 days and tabulated from Table 2 to Table 8. However, depending on the temperature and environmental circumstances, the average battery charge is 3 to 5 hours. The solar radiation reached its optimum range at 12 and 1 o’clock afternoon which has been analyzed and tabulated. This device is fully modular, so it can be assembled and disassembled. Thus, it’s free and saves electricity costs in our house and we can get much healthier foods from the night markets.